VLADIMIR ONUPHRIEVICH KOVALEVSKY - THE FOUNDER OF THE EVOLUTIONARY PALEONTOLOGY (TO THE 175TH ANNIVERSARY) - V. N. Komarov (Известия высших учебных заведений: Геология и разведка, 2016)
The 175th anniversary of Vladimir Onuphrievich Kovalevsky, an outstanding Russian scientist, considered as a founder of evolutionary paleontology, is celebrated in 2017 year. Before the classical works of V.O. Kovalevsky, paleontology dealt predominantly with the description of the fossils. V.O. Kovalevsky raised the paleontology to the level of science about the historical evolution of the organisms. With the correspondence to his evolutionary-paleontological method, Kovalevsky describes the modification of the fossil ungulates and refers them to the modifying environment and transformation of the corresponded organs in phylogenies.